Metabolic syndrome: unravelling or unravelled?. Issue 7 (July 2019) - Baranowski, Elizabeth S.; Barrett, Timothy G.
Abstract: Metabolic syndrome comprises the association of risk factors for future cardiovascular disease (hypertension, altered glucose metabolism, dyslipidaemia, and abdominal obesity). It is thought to affect up to 40% of overweight or obese children in the UK. This has coincided with a rise in obesity-related type 2 diabetes in children. The characterisation of co-morbidities has improved since the last review in 2015. This review discusses some of the current theories about disease mechanisms, and reviews the current guidelines to propose a practical screening checklist for identifying and managing affected children. Metabolic syndrome in children impacts on all of us as paediatricians. Careful attention to screening for and management of complications, and consistent diet, exercise and lifestyle advice, can minimise the effects of our obesogenic environment.